Laryngeal Tissue Engineering using Rabbit Adipose Derived Stem Cells in Fibrin: A Pre-Clinical Model - Shiba Travis; Hardy Jordan; Long Jennifer (Journal of Otolaryngology Advances, 2015)
Vocal fold scarring is a clinical problem without reliable treatment. Tissue engineering of a vocal fold replacement is an exciting potential treatment for vocal fold scars that involve multiple layers of the vocal fold. Human adipose-derived stem cells (ASC) were previously used to produce a promising vocal fold cover layer replacement. However, relevant in vivo studies are needed before human application, and implanting the human cells in animal larynges would introduce significant risk and data confounding. We therefore report here the development of a construct based on rabbit ASC with the potential for use in pre-clinical implantation studies. Rabbit ASC were isolated and cultured in a three-dimensional fibrin matrix to create an implantable construct resembling the vocal fold mucosa. Key differences between the human cell and the rabbit cell models are highlighted.
Keywords: vocal fold